Renewable energy from biogas generated by sewage sludge – relationship between sludge volume and power generated / Suzana Ramli ... [et al.] - Ramli, Suzana; Mohd Baki, Aminuddin; Ayub, Muhamad Azmi; Abdul Talib, Suhaimi; Mohd Tajuddin, Ramlah; Atan, Ismail; Jaafar, Jurina; Abdullah, Nur Aziafwani (Research Management Institute (RMI), 2008)
Biogas is a product of decomposition of organic matter during the process of anaerobic digestion (AD). The main components are methane and carbon dioxide. The methane content in the biogas enables it to be used as fuel which can be converted to heat and electricity. The biogas generated by the anaerobic digesters has the potential to be redirected from the flaring facilities to renewable energy (RE) facilities. The biogas may then be used to generate electricity, which in turn can operate the sewage treatment plant (STP) itself. However, feedbacks from the sewerage industry indicated that heavy investments are needed for any RE initiatives on biogas generated by sewage sludge. In order to find the cost effective way of generating energy from biogas, fundamental relationships are necessary to enable development of prototype in the future. Thus, this paper presents a study to establish the relationship between the volume of sludge and the amount of power and energy that can be generated.